The Image of Women Figures in Folklore of Kudus Kulon’s Toponyms: A Linguistics Anthropology Study - Ratna Muthia; Fatah Syukur (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
This study aims to explore the image of women figures in folklore relating to the naming of a place (toponym) in the Kudus Kulon area. This study was carried out with a linguistic anthropology approach, which focuses on language as a set of symbolic resources that enter the constitution or social and individual representations in the real world. The results of this study are as follows: 1) the origin of the toponym, i.e. the name and the activity of the women figures; 2) the role of women figures, consisting of the main and side characters; 3) the relation between female and male figures in toponym can be divided into two: (a) women figures representing the husband and (b) women figures representing themselves; 4) opportunities for women figures, including opportunities to solve problems, opportunities to move according to their interests, and opportunities to participate in public roles; 5) influences of women figures, including influences on spirituality, influences on economic activities, and influences on culture.